Comparative phylogenetic analysis of oolong tea (Phoenix Dancong tea) using complete chloroplast genome sequences. Issue 12 (December 2022) - Liu, Yaqun; Lin, Liyun; Yang, Dongjuan; Zou, Xianghui; Zhang, Zhenxia; Liu, Mouquan; Lin, Min; Zheng, Yuzhong
Abstract: Phoenix Dancong tea, a variety of oolong tea, is produced in Chaozhou, Guangdong Province, China, and is characterized by numerous hybridizations and polyploidization. To assess the genetic diversity and phylogenetic relationships among Phoenix Dancong tea and other oolong teas, an integrated circular chloroplast genome was constructed for thirty species of Phoenix Dancong tea from Chaozhou. The genome of Phoenix dancong tea is a circular molecule of 157, 041–157, 137 bp, with a pair of inverted repeats (26, 072-26, 610 bp each) separated by a large single copy (86, 615-86, 658 bp) and small single copy (18, 264-18, 284 bp). A total of 135 unique genes were encoded, including 90 protein coding genes, 37 tRNAs and 8 rRNAs. A comparative analysis with the other seven species in the oolong tea family that have been sequenced to date revealed similarities in structural organization, gene content and arrangement. Repeated sequence analysis identified 17–23 tandem repeats, 20–24 forward repeats and 25–27 palindromic repeats. Additionally, a total of 65–70 simple sequence repeats were detected, with mononucleotide repeats being the most common. Phylogenetic analyses showed that Phoenix Dancong tea and Fujian oolong tea were clustered with other cultivated Camellia sinensis in the genus Camellia of the family Theaceae, while the two oolong tea species were relatively independently cross-embedded in the genus, Camellia . Close genetic relationships were observed between Phoenix Dancong tea and other oolong teas, and the overall chloroplast genomes of oolong tea showed patterns with low variations and conserved evolution. The availability of Phoenix Dancong tea chloroplast genomes not only elucidated the relationship among oolong teas from different origins in Guangdong and Fujian but also provided valuable genetic resources to assist further molecular studies on the taxonomic and phylogenomic resolution of the genus Camellia . Abstract : Phoenix Dancong tea; Oolong tea; Chloroplast genome; Genomic structure; Repeat analysis; Phylogeny.